Frecuencia de asimetrías maxilomandibulares en una muestra de radiografías panorámicas de pacientes pediátricos - Bolivar, Diego; Zuñiga, Claudia; Ortiz, Paola; López, Diego; Baquero, Camilo (Revista Estomatología, 1999)
Subtle asymmetric variations of contralateral structures of the head an face occur commonly in the general population. This exploratory study pretends to determine the frecuency of significant maxilomandibular asymmetries detected radiographically in a pediatric patients sample. With this purpose panoramic radiographies of patients from six to ten years old were chosen. A modified Levandoski Panoramic Analysis was used to determine radiographic asymmetries. A considerable frecuency of maxilomadibular asymmetry might suggest, there is a need to apply a modified Levandoski analysis in a routinary manner, in order to achieve integral diagnosis in pediatric patients.